The 3D Seismic Survey Design of South Walio Offshore, Indonesia: Optimizing the 3D Survey Design Parameters - Wahyu Triyoso; Supriyono Supriyono; Firman Saifuddin Akbar; Madaniya Oktariena; Sri Lestari; Benny Eza Yusuf; Donny Miraza (Scientific Contributions Oil and Gas, 2023)
The background of this research is to support the plan to carry out 3D seismic acquisition in the Salawati Kepala Burung Working Area located in Sorong Regency. The 3D seismic design study was applied to better understand the physical properties of the Mesozoic clastic reservoir in the Salawati basin and its surroundings, especially in the offshore area. The study aims to evaluate the parameters of a reliable 3D seismic acquisition design to meet efficiency in financing in realizing the 3D seismic data acquisition program. Determine the recording parameters to image the Kais Formation and Waripi Formation targets by building a geophysical analysis model using existing 2D data and well-log information. Based on this model, using the Kais and Waripi formation properties to calculate and analyze vertical and horizontal resolution, bin size, aperture migration, and maximum offset. Synthetic acquisition 2D modeling is applied in this study to perform vertical and horizontal resolution analysis and obtain optimum and reliable bin size parameters and aperture migration. With this knowledge, we calculate the theoretical parameters of the survey. After determining the most critical theoretical parameters of the study, the next step is to determine the distance between the source and receiver. Then define the recording template. It is done by considering the bin size for the 3D model, offset boundaries, and suitable folds for inner targets. In the second, an analysis of the other two most important attributes is carried out, namely the offset and azimuth distribution. It is realized that every 3D survey design compromises technical factors affecting 3D survey costs starting from the technical requirements of field activities. The results of this study are recommendations and suggestions for two main alternative models of recording parameters and templates in the form of ideal source-receiver layout models, namely orthogonal and diagonal, and the minimum prerequisites that are expected to be able to map and determine the characteristics of the shallow and deep play type models in the South Walio offshore areas.